The Effect of Burning Temperature and Solution Concentration on the Characteristic of Silica Gel Extracted from Rice Husk Ash - Chiew, Chee Seng (Universiti Teknologi PETRONAS, 2016)
Combustion of rice husk to generate energy results in the waste product called rice husk ash (RHA). RHA is potential bio-fertilizer for plant as it contain over 90% of silica and silica is proved that it can provide substantial benefits to many crops. Silica are being extracted from RHA in the form of silica gel by leaching process. The extraction of silica gel is more effective after reheating RHA by thermal treatment with temperatures ranging from 500-1400ºC. This work focused on interrelationship of the burning temperature of RHA for 6 hours and concentration of sodium hydroxide which will affect the silica content of the silica gel extraction. It is done by investigate the effect of burning temperature and concentration of basic solution on extraction of silica gel from rice husk ash and the optimum condition for silica gel extraction from RHA as bio-fertilizer for plants.